2016
DOI: 10.18632/oncotarget.13375
|View full text |Cite
|
Sign up to set email alerts
|

P2rx4 deficiency in mice alleviates allergen-induced airway inflammation

Abstract: Compelling evidences point out a crucial role for extracellular nucleotides such as adenosine triphosphate (ATP) during inflammatory conditions. Once released into the extracellular space, ATP modulates migration, maturation and function of various inflammatory cells via activating of purinergic receptors of the P2Y- and P2X- family. P2RX4 is an ATP-guided ion channel expressed on structural cells such as alveolar epithelial and smooth muscle cells as well as inflammatory cells including macrophages, dendritic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 40 publications
(68 reference statements)
2
44
1
Order By: Relevance
“…This finding was consistent in both male and female mice. Similar observations have been made in prior studies: BMDCs from P2rx4 tm1Rass were reported to exhibit a decreased P2rx7 mRNA expression (Zech et al, 2016) and macrophages from P2rx4 tm1Rass showed a reduced pore formation capacity in response to ATP stimulation (Pérez-Flores et al, 2015). At last, our finding that microglia from B6 P2X4ko mice express similar level of P2X7 compared to B6 WT also confirms an earlier report (Ulmann et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…This finding was consistent in both male and female mice. Similar observations have been made in prior studies: BMDCs from P2rx4 tm1Rass were reported to exhibit a decreased P2rx7 mRNA expression (Zech et al, 2016) and macrophages from P2rx4 tm1Rass showed a reduced pore formation capacity in response to ATP stimulation (Pérez-Flores et al, 2015). At last, our finding that microglia from B6 P2X4ko mice express similar level of P2X7 compared to B6 WT also confirms an earlier report (Ulmann et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…In lung epithelial cells, P2X4 is associated with both exocytosis of lung surfactants and alveolar fluid transport [28] , making it a key player in airway homeostasis. It is elevated in asthmatic patients and in a mouse model of asthmatic disease [108] . In the mouse model of asthma, P2X4 antagonists can be used to efficiently alleviate many of the symptoms: eosinophilia, inflammation, mucus production, and cellular infiltration in the airway [108] , [109] .…”
Section: Other Roles Of P2x4mentioning
confidence: 99%
“…It is elevated in asthmatic patients and in a mouse model of asthmatic disease [108] . In the mouse model of asthma, P2X4 antagonists can be used to efficiently alleviate many of the symptoms: eosinophilia, inflammation, mucus production, and cellular infiltration in the airway [108] , [109] . P2X4-deficient mice are also less prone to Th2 responses, the same can be observed in mice which received an adoptive transfer of P2X4-deficient bone marrow cells [108] .…”
Section: Other Roles Of P2x4mentioning
confidence: 99%
“…These changes are accompanied by upregulation and activation of microglial P2X4Rs (Vazquez-Villoldo et al, 2014). Prior studies using global P2X4R knockout (KO) mice showed diminished inflammasome signaling following spinal cord injury or allergen-induced airway inflammation (de Rivero Vaccari et al, 2012; Zech et al, 2016). In these injury models, P2X4R-positive leukocytes (i.e., macrophages, dendritic cells, and T cells) are the main sources of pro-inflammatory cytokine release.…”
Section: Introductionmentioning
confidence: 99%